Gojek -Tokopedia: the desire of Micro, Small and Medium Enterprises to become merchant members - Dewi, Dyah Ayu Rachmawati; Santoso, Ignatius Hari (Sebelas Maret Business Review, 2022)
This research aims to identify factors that significantly impact the interest in adopting Tokopedia as the marketplace of choice for micro, small and medium enterprises. By using 100 samples with criteria not yet registered as a merchant member at Tokopedia, this research proves that of the three variables tested, only one variable has been shown to have a significant impact, namely brand awareness. While the other two variables, namely brand ambassador and electronic WoM, had no significant effect. Before running the path analysis using the Smart PLS program, the researcher tested the validity and reliability with the outer loading, average variance extracted, and composite reliability parameters sequentially. Thus, based on the results of this research, Tokopedia can create other activities that encourage increased brand awareness of the brand.